Pricing Hurricane Bonds Using a Physically Based Option Pricing Approach. Issue 1 (2nd January 2022) - Chang, Carolyn W.; Chang, Jack S. K.; Yu, Min-Teh
Abstract : Hurricane bonds are unique in that they are structured with a dual exercise condition: a physically based condition that the underlying hurricane makes landfall at a prespecified location, and a standard moneyness condition that they end in the money. As the time of landfall is uncertain, their maturities are also uniquely random. This research thus proposes a modeling methodology to solve this option-pricing problem—that is, to price hurricane bonds at the nexus of atmospheric science and finance by integrating hurricane risk modeling and option pricing modeling. We resolve this dual exercise/random maturity issue by implementing a coupled hurricane generator to simulate hurricane synthetic tracks, intensity, radius, two-dimensional wind fields, and hurricane-index value evolution along the tracks. We price the increasingly popular parametric and parametric-index hurricane bonds by Monte Carlo simulations, as the underlying hurricane indices are untraded and thus replication pricing is not viable.